IOT BASED ALARM SYSTEM - Prof. Pawar V.D; Miss. Narune A.G; Miss. Kanagi S.S (International Engineering Journal For Research & Development, 2020)
Now a day college bells are operated manually. It replaces the manual switching of the Bell in the College. This project is to implement IOT Based Automatic Alarm system takes over the task of ringing the bell at predetermined time. It saves manpower, time and ultimately money and also gives highest accuracy. The main components of this system are WIFI module, servo motor, and bell.When this time equals to the Bell Ringing time, then the Relay for the Bell is switched on. The Bell Ringing time can be edited at any Time, so that it can be used at Normal Class Timings as well as Exam Times. Required power supply is given through power supply unit. Adriano keeps control on function of system. The main aim of this project is to implement IOT Based Automatic Alarm system using Adriano UNO. The main task of this system is to ring the bell at predetermined time with accuracy and without any human intervention.